Engagement, academic satisfaction and moral values in university students - Reséndiz Chávez, Jaquelinne (Consorcio de Universidades Mexicanas A.C., 2017)
In recent years, higher education in Mexico has increased its demand and being an important element in the development of our society, has generated the interest to study the elements and actors that converge in it, reason why, the aim of this Study was to correlate the variables of engagement, moral values and academic satisfaction in university students of psychology at the Universidad Autónoma del Estado de Hidalgo. The sample was 215 students of the Institute of Health Sciences, to whom they were applied, the Utrecht Work Engagement Scale-Mexico (UWES-S Mexico), the Scale of Academic Satisfaction and the Moral Values Questionnaire in Training and Exercise Professional. The statistical test, Pearson product-moment, showed the existence of statistically significant correlations between the three variables, however, were not present in all factors. In addition, the correlations were low, which means that the influence between the variables is small, but it is definitely present. These findings bring new elements, from psychology, to the existing literature of moral values and academic satisfaction, and allow a better understanding of engagement by integrating new variables into their study.